Rubber rampage: the era that produced vulcanized rubber - Hayes, Rachel (Kansas State University. K-State Libraries, 2013)
Rubber, a waterproof gum, was demanded by many in the early 1830’s. While useful as a waterproof, elastic fabric in its flexible state which is at room temperature, the rubber froze in the winter and turned sticky in the summer. During this era, many knew that whoever discovered the stable state would gain an abundant fortune. This is what Charles Goodyear achieved in 1839 by adding sulfur to the natural rubber; this process is now known as vulcanization. This scientific breakthrough revolutionized the automobile industry. Society had been using the iron wheel since 1000 BC which was an extremely rickety trail ride. The newly stabilized rubber absorbed the shock from the imperfections in the road in the form of a tire; thus, creating a more stable ride. This heighted the urge for the public to create gas powered vehicles. Everything about the discovery of rubber and vulcanization drove the automobile industry into the astounding business that it currently is.
Kirmser Undergraduate Research Award - Individual Freshman category, grand prize
Citation: Hayes, R. (2013) Rubber rampage: the era that produced vulcanized rubber. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Rubber; Vulcanization; Charles Goodyear; Tires; Automobiles